Cold chains in Hanoi and Bangkok: Changing systems of provision and practice. (August 2019) - Rinkinen, Jenny; Shove, Elizabeth; Smits, Mattijs
We know that patterns of domestic consumption are situated within broader systems of provision and that home appliances like the fridge freezer bridge between practices of cooking, shopping and eating, on one hand, and increasingly global systems of food production, distribution and diet on the other. In analysing the uses of fridge freezers in Hanoi and Bangkok as expressions, in microcosm, of complex and evolving processes of urbanisation and food provisioning, this article provides new insight into how specific configurations, dependencies and patterns of consumption take hold and how they vary and change. Our analysis of systems and practices in flux has the dual function of showing how household strategies reflect and contribute to more extensive transformations, and of demonstrating how these are shaped by ongoing tensions and relations between new and established forms of urban food supply and associated concepts of freshness and safety. The result is a subtle account of the multiple routes through which consumer 'needs' evolve.